Measuring satisfaction with life-construct among university students during Covid-19 pandemic in Sabah, Malaysia - Mohd Dahlan A. Malek; Ida Shafinaz Mohamed Kamil; Adi Fahrudin; Adeymend Reny Japil (AMER (Association of Malaysian Environment-Behaviour Researchers), and cE-Bs (Centre for Environment-Behaviour Studies), College of Built Environment, Universiti Teknologi MARA, Malaysia, 2024)
This study aimed to develop a dependable and valid tool for assessing Satisfaction with Life (SWL) constructs among 108 university students in Sabah, Malaysia. The exploratory factor analysis (EFA) procedure was employed for this purpose. Utilizing the Principal Component Analysis (PCA) with Varimax Rotation as the extraction method, a SWL construct component was identified with an eigenvalue of 3.1. This component accounted for 62% of the variance. The SWL construct demonstrated a Cronbach's alpha value of .817, indicating good internal consistency. The scale's development and validation process affirmed its reliability and stability when applied to university student samples.